"World's pharmacy" faces new challenges from Western drug companies. (17th September 2012) - Jack, Andrew
Abstract : As it becomes a global battleground for the fight over intellectual property rights, is India's role as the "world's pharmacy" under threat? And what effect will this have on affordable access to medicines? Andrew Jack reports